Relating folksonomies with Dublin Core - Catarino, Maria Elisabete (2008)
Folksonomy is the result of describing Web resources with tags created by Web users. Although it has become a rich basis for the description of resources, in general terms it is not being conveniently integrated in metadata. However, if the appropriate metadata elements are identified, then further work may be done in order to automatically assign tags to these elements (RDF properties) and use them in Semantic Web applications. This article presents research carried out to continue the project Kinds of Tags, which intends to identify elements required for metadata originating from folksonomies and to propose an application profile for DC Social Tagging. It will provide information that may be used by software applications to assign tags to metadata elements and, therefore, means for tags to be conveniently gathered by metadata interoperability tools. Despite the unquestionably high value of DC and the significance of the already existing properties in DC Terms, the pilot study show revealed a significant number of tags for which no corresponding properties yet existed. A need for new properties, such as Action, Depth, Rate, and Utility was determined. Those potential new properties will have to be validated in a later stage by the DC Social Tagging Community.